Multimodal prediction of neoadjuvant treatment outcome by serial FDG PET and MRI in women with locally advanced breast cancer - Kazerouni, Anum S; Peterson, Lanell M; Jenkins, Isaac; Novakova-Jiresova, Alena; Linden, Hannah M; Gralow, Julie R; Hockenbery, David M; Mankoff, David A; Porter, Peggy L; Partridge, Savannah C; Specht, Jennifer M (Breast cancer research, 2023)
PURPOSE: To investigate combined MRI and 18F-FDG PET for assessing breast tumor metabolism/perfusion mismatch and predicting pathological response and recurrence-free survival (RFS) in women treated for breast cancer. METHODS: Patients undergoing neoadjuvant chemotherapy (NAC) for locally-advanced breast cancer were imaged at three timepoints (pre, mid, and post-NAC), prior to surgery. Imaging included diffusion-weighted and dynamic contrast-enhanced (DCE-) MRI and quantitative 18F-FDG PET. Tumor imaging measures included apparent diffusion coefficient, peak percent enhancement (PE), peak signal enhancement ratio (SER), functional tumor volume, and washout volume on MRI and standardized uptake value (SUVmax), glucose delivery (K1) and FDG metabolic rate (MRFDG) on PET, with percentage changes from baseline calculated at mid- and post-NAC. Associations of imaging measures with pathological response (residual cancer burden [RCB] 0/I vs. II/III) and RFS were evaluated. RESULTS: Thirty-five patients with stage II/III invasive breast cancer were enrolled in the prospective study (median age: 43, range: 31-66 years, RCB 0/I: N = 11/35, 31%). Baseline imaging metrics were not significantly associated with pathologic response or RFS (p > 0.05). Greater mid-treatment decreases in peak PE, along with greater post-treatment decreases in several DCE-MRI and 18F-FDG PET measures were associated with RCB 0/I after NAC (p < 0.05). Additionally, greater mid- and post-treatment decreases in DCE-MRI (peak SER, washout volume) and 18F-FDG PET (K1) were predictive of prolonged RFS. Mid-treatment decreases in metabolism/perfusion ratios (MRFDG/peak PE, MRFDG/peak SER) were associated with improved RFS. CONCLUSION: Mid-treatment changes in both PET and MRI measures were predictive of RCB status and RFS following NAC. Specifically, our results indicate a complementary relationship between DCE-MRI and 18F-FDG PET metrics and potential value of metabolism/perfusion mismatch as a marker of patient outcome.
Keywords: Fluorodeoxyglucose F18; prospektivní studie; nádory prsu; Dynamic 18F-FDG PET; Treatment Outcome; Dynamic contrast enhanced MRI; Radiopharmaceuticals; radiofarmaka; dospělí; Recurrence; lidé; Diffusion weighted MRI; fluorodeoxyglukosa F18; Prospective Studies; Chemotherapy response; Positron-Emission Tomography; Breast Neoplasms; ženské pohlaví; magnetická rezonanční tomografie; pozitronová emisní tomografie; výsledek terapie; Neoadjuvant Therapy; neoadjuvantní terapie; Adult; Humans; Magnetic Resonance Imaging; Female